Rheological Characteristics and Micro-mechanism of Regenerated Asphalt from Different Viscosity Furfural Extract Oils - Luan, Wenxue; Dai, Wenting (Journal of Research in Science and Engineering, 2026)
Existing research indicates that furfural extracted oil (FEO) can regenerate aged asphalt. However, previous studies have lacked an investigation into the impact of the viscosity of FEO on the regeneration effect of asphalt. Therefore, this paper proposes the use of two viscosities of FEO to regenerate asphalt and compares the effects of different viscosities of FEO on the regeneration of aged asphalt. The basic physical properties of regenerated asphalt containing 10% and 15% of FEO with viscosities of 3.9 and 17-23 were compared using penetration, softening point, and ductility tests. Rheological characteristics were examined through dynamic shear rheometry and bending beam rheometry. Finally, the regeneration mechanism was analyzed using Fourier transform infrared spectroscopy. The findings revealed that FEO can effectively regenerate aged asphalt. As the viscosity of the extracted oil increased, the high-temperature deformation resistance of the regenerated asphalt improved, while its medium-temperature fatigue resistance and low-temperature cracking resistance decreased. Ultimately, it was determined that the ability of FEO to regenerate aged asphalt is due to its addition of small molecular components that are deficient in the aged asphalt. The lower polarity of the low-viscosity FEO allows for better reduction of the solubility of the aged asphalt compared to the higher viscosity oil, thus enhancing the solubility that decreases during the aging process due to increased polarity.